PD-1 and CTLA-4 exert additive control of effector regulatory T cells at homeostasis - Pereira, Joseph A.; Lanzar, Zachary; Clark, Joseph T.; Hart, Andrew P.; Douglas, Bonnie B.; Shallberg, Lindsey; O’Dea, Keenan; Christian, David A.; Hunter, Christopher A. (Frontiers in Immunology, 2023)
At homeostasis, a substantial proportion of Foxp3+ T regulatory cells (Tregs) have an activated phenotype associated with enhanced TCR signals and these effector Treg cells (eTregs) co-express elevated levels of PD-1 and CTLA-4. Short term in vivo blockade of the PD-1 or CTLA-4 pathways results in increased eTreg populations, while combination blockade of both pathways had an additive effect. Mechanistically, combination blockade resulted in a reduction of suppressive phospho-SHP2 Y580 in eTreg cells which was associated with increased proliferation, enhanced production of IL-10, and reduced dendritic cell and macrophage expression of CD80 and MHC-II. Thus, at homeostasis, PD-1 and CTLA-4 function additively to regulate eTreg function and the ability to target these pathways in Treg cells may be useful to modulate inflammation.